First-in-Man Noninvasive Initial Diagnostic Approach of Primary CNS Lymphoma Versus Glioblastoma Using PET With 18F-Fludarabine and l-[methyl-11C]Methionine. (29th August 2022) - Postnov, Andrey; Toutain, Jérôme; Pronin, Igor; Valable, Samuel; Gourand, Fabienne; Kalaeva, Diana; Vikhrova, Nina; Pyzhik, Elena; Guillouet, Stéphane; Kobyakov, Grigoriy; Khokholova, Ekaterina; Pitskhelauri, David; et al.
Abstract : Objectives: This study sought to assess 18 F-fludarabine ( 18 F-FLUDA) PET/CT's ability in differentiating primary central nervous system lymphomas (PCNSLs) from glioblastoma multiformes (GBMs). Patients and Methods: Patients harboring either PCNSL (n = 8) before any treatment, PCNSL treated using corticosteroids (PCNSLh; n = 10), or GBM (n = 13) were investigated with conventional MRI and PET/CT, using 11 C-MET and 18 F-FLUDA. The main parameters measured with each tracer were SUVT and T/N ratios for the first 30 minutes of 11 C-MET acquisition, as well as at 3 different times after 18 F-FLUDA injection. The early 18 F-FLUDA uptake within the first minute of injection was equally considered, whereas this parameter was combined with the later uptakes to obtain R FLUDA 2 and R FLUDA 3 ratios. Results: No significant differences in 11 C-MET uptakes were observed among PCNSL, PCNSLh, and GBM. With 18 F-FLUDA, a clear difference in dynamic GBM uptake was observed, which decreased over time after an early maximum, as compared with that of PCNSL, which steadily increased over time, PCNSLh exhibiting intermediate values. The most discriminative parameters consisting of R FLUDA 2 and R FLUDA 3 integrated the early tracer uptake (first 60 seconds), thereby provided 100% specificity and sensitivity. Conclusions: 18 F-FLUDA was shown to likely be a promising radiopharmaceutical for differentiating PCNSL from other malignancies, although a pretreatment with corticosteroids might compromise this differential diagnostic ability. The diagnostic role of 18 F-FLUDA should be further investigating, along with its potential of defining therapeutic strategies in patients with PCNSL, while assessing the treatments' effectiveness.